DIFFERENTIAL EXPRESSION OF CHICKEN BRAIN PROTEINS DURING DEVELOPMENT - DR. M.NAVEEN SWAROOP; DR. ALOK BARATI (International Journal of Pharma and Bio Sciences, 2012)
Understanding the proteins role and their spatiotemporal relationships in the development of brain will enrich the knowledge about structure – function relationships, control of productive traits, and neurological diseases. This study explores the different proteins involved in the development of the brain. Brains from Vanaraja breed embryos were collected from days 2 to 13continuously; from days 15,17,19,21 and from 6weeks birds and analyzed by SDS PAGE (5% stacking gel and 12% resolving gel). 27 proteins were differentially expressed in different developmental stages. Some of these proteins are 160kDa, 145kDa, 120-123kda, 100kDa, 92-102kDa, 97kDa, 80kDa, 66kDa, 60kDa, 58kDa, 50kDa, 34kDa, 22-25kDa, 20kDa, 16kDa, 14kDa. There was a progressive increase in the expression levels of higher molecular weights with advancing age. During early development of brain, may be low molecular weight proteins are playing a vital role in neural induction, anterio –posterior patterning, dorsovental patterning and cell differentiation.